The Effect of Carrageenan on the Textural and Sensory Characteristics of Mackerel Tuna Fishballs - Yudhistira, B; Affandi, D R; Kurniasari, R Y; Sanjaya, A P (International Journal of Psychosocial Rehabilitation, 2020)
Mackerel tuna is one of the marines catches with a high production amount in Indonesia, but lacking in its utilization. Diversification of Mackerel tuna can be made with processed into fishballs. The used of Mackerel tuna surimi as raw material and the addition of carrageenan is expected to improve the texture so it can be accepted sensory. Arrowroot flour as substitution of tapioca starch is useful to increased the nutritional and functional content of fishballs. This research aims to determine the effect of the addition of carrageenan to the characteristics of texture and sensory fishballs. This research used completely randomizes design (CDR) with one factor of carrageenan addition variations i.e. 0.5%; 1% and 1.5%. Data were analyzed statistically by the method of one-way Analysis of Variance (ANOVA). The result of this study showed that the addition of carrageenan gave significant different effect on the physical characteristics such as water holding capacity, cohesiveness, chewiness, and springiness, while not significantly different to the color of fishballs. Sensory test results showed that overall, fishballs with 0.5% addition of carrageenan.